2023
DOI: 10.3390/antiox12030729
|View full text |Cite
|
Sign up to set email alerts
|

Increased Renal Medullary NOX-4 in Female but Not Male Mice during the Early Phase of Type 1 Diabetes: Potential Role of ROS in Upregulation of TGF-β1 and Fibronectin in Collecting Duct Cells

Abstract: Chronic diabetes mellitus (DM) can lead to kidney damage associated with increased reactive oxygen species (ROS), proteinuria, and tubular damage. Altered protein expression levels of transforming growth factor-beta 1 (TGF-β1), fibronectin, and renal NADPH oxidase (NOX-4) are associated with the profibrotic phenotype in renal tubular cells. NOX-4 is one of the primary sources of ROS in the diabetic kidney and responsible for the induction of profibrotic factors in collecting duct (CD) cells. The renal medulla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Conversely, inhibition of these particular sources (processes) of ROS generation can exert beneficial effects against cell/tissue damage. In this Special Issue, Casado-Barragán et al [19] showed that NOX-4 is a primary source of ROS responsible for the induction of profibrotic factors in the renal medulla. Consequently, these factors cause chronic kidney disease differently regulated in male and female mice and can be alleviated by specific NOX4 inhibitors.…”
Section: Antioxidants Reduce the Risk Of Chronic Diseasesmentioning
confidence: 99%
“…Conversely, inhibition of these particular sources (processes) of ROS generation can exert beneficial effects against cell/tissue damage. In this Special Issue, Casado-Barragán et al [19] showed that NOX-4 is a primary source of ROS responsible for the induction of profibrotic factors in the renal medulla. Consequently, these factors cause chronic kidney disease differently regulated in male and female mice and can be alleviated by specific NOX4 inhibitors.…”
Section: Antioxidants Reduce the Risk Of Chronic Diseasesmentioning
confidence: 99%